The Effect of Operating in Many Realities on Memory: An Experiment on Memory Recognition in Extended Realities - Xi Nannan; Chen Juan; Gama Filipe; Korkeila Henry; Hamari Juho (United States, 2022)
Extended reality (XR) such as VR and AR have been increasingly adopted across domains in cognitively challenging activities such as learning, shopping, and gaming among others. There are a few concerns about the inferior cognitive affordance of XR-mediated functioning, e.g., with respect to memory retention. For better understanding how different XR technologies influence memory performance (e.g., recognition), we examine the effects of VR and AR -mediation on the ability to remember (i.e., recognize afterward) text and image-based information based on a 2 × 2 between-subject experiment (n = 155). The results indicate that VR had a negative main effect on text-based information recognition but no effect on image-based information recognition. AR had no significant main effect on the recognition of either information types. Overall, the findings as further supported by the interaction effects analysis, suggest that for memory recognition, it is always best to have a fully physical (no-AR & no-VR) or fully digital environment (AR & VR) compared to having either VR or AR alone.
Proceedings of the 54th Hawaii International Conference on System Sciences 2021